John Charles McGregor and excerpts from his diary - McGregor, John Charles (Electronic version published by Vancouver Island University, 1968)
Audio recording and transcript of William Barraclough's 1968 presentation to the Nanaimo Historical Society about John Charles McGregor. Barraclough gives a brief history of McGregor and his family and then reads excerpts from McGregor's diary which are the account of McGregor's walk out of the Klondike: a 600 mile journey in 1899 from Dawson City to Skagway. https://library.viu.ca/libinfo/harmfullanguagestatement https://viurrspace.ca/bitstream/handle/10613/205/NanaimoHistoryMcGregor18.pdf?sequence=4 Recorded for the Nanaimo Historical Society on July 22, 1968.